Higher consumption of ultra-processed food is associated with cardiovascular risk in Korean adults: KNHANES 2016–2018 - Jung, Sukyoung; Jang, Eunjin; Lee, Hyeongyeong; Kim, Jee Young; Park, Sohyun (Frontiers in Nutrition, 2023)
Background: Excessive consumption of ultra-processed foods (UPFs) has been linked to an increased risk of cardiovascular disease. We aimed to investigate the association between the percentage of energy intake from UPFs and the American Heart Association's cardiovascular health (CVH) metrics in Korean adults.Methods: This study analyzed adults aged 40 years and older using data from the Korean National Health and Nutrition Examination Survey 2016Survey -2018 (n=9,351) (n=9,351). All foods or beverages reported in a 24-hour dietary recall were categorized using the NOVA system, and the percentage of energy from UPFs was calculated. Each CVH metric was scored 0-2 (poor, intermediate, ideal). The sum of six component scores was classified as inadequate, average, or optimum. Multinomial logistic regression models were used to estimate the covariateadjusted odds ratios (ORs) and 95% confidence intervals (CIs) for inadequate and average CVH versus optimum CVH.The mean percentage of energy from UPFs was 24.2%. After adjusting for covariates, participants in the highest UPF quartile had 26% higher odds of having inadequate CVH than those in the lowest quartile (OR 1.26, 95% CI 0.94-1.69, P-trend=0.03). The percentage of energy from UPFs was positively associated with current smoking, physical inactivity, body mass index, and total cholesterol and was inversely associated with blood pressure and fasting glucose.The percentage of energy from UPFs accounted for one-fourth of total calorie intake in Korean adults aged 40 years and older. Higher UPF consumption was associated with poorer CVH, underscoring the potential of limiting UPF consumption as a preventative measure for cardiovascular diseases.